2008
DOI: 10.2174/1874158400802010089
|View full text |Cite
|
Sign up to set email alerts
|

Size Dependent Hardness of Polyamide/Imide

Abstract: Indentation experiments with indentation depths in the nano-and micrometer ranges in the literature have shown that that an indentation size effect similar to metals is present in polymers. In this paper we present indentation experiments of a polyamide/imide polymer of indentation depths in the range of 1 to 30 microns. An increase in hardness of about 70% was observed at small indentation depths compared to hardness at large indentation depths. The indentation results are discussed with respect to an indenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 13 publications
2
11
0
Order By: Relevance
“…Such behavior is well known and widely observed in other material tests such as simple tensile tests [Lemaitre and Chaboche 1990]. The values in Figure 3, however, also show a decrease of η e with decreasing h, and therefore the dissipation of the indentation work increases with decreasing h. Similar tendencies have also been observed in other polymers [Briscoe et al 1998;Tatiraju et al 2008]. The magnitude with which η e decreases is more pronounced at shorter loading times.…”
Section: Indentation Experimentssupporting
confidence: 82%
“…Such behavior is well known and widely observed in other material tests such as simple tensile tests [Lemaitre and Chaboche 1990]. The values in Figure 3, however, also show a decrease of η e with decreasing h, and therefore the dissipation of the indentation work increases with decreasing h. Similar tendencies have also been observed in other polymers [Briscoe et al 1998;Tatiraju et al 2008]. The magnitude with which η e decreases is more pronounced at shorter loading times.…”
Section: Indentation Experimentssupporting
confidence: 82%
“…Depth sensing indentation testing has been widely applied to determine hardness, elastic modulus, as well as to study deformation mechanisms at micro-and nanometer length scales. Numerous indentation experiments conducted on metals [1][2][3] and polymers [4][5][6][7][8][9][10][11][12][13][14][15][16] demonstrated that the hardness is significantly higher at small probing depths. In [11,13,17] the length scale dependence in polymers has been experimentally observed in elastic deformation, which is in contrast to metals, where length scale effects were observed in plastic deformation and usually attributed to geometrically necessary dislocations [2].…”
Section: Introductionmentioning
confidence: 99%
“…In [11,13,17] the length scale dependence in polymers has been experimentally observed in elastic deformation, which is in contrast to metals, where length scale effects were observed in plastic deformation and usually attributed to geometrically necessary dislocations [2]. Although there is mounting experimental evidence for size effects in polymers [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], compared to metals, length scale dependent deformation in polymers is arguably not well understood and there are only few length scale dependent theories suggested in the literature [5,6,21,22] for polymers.…”
Section: Introductionmentioning
confidence: 99%
“…What we observed, however, appears at best weak effects whereas there are obvious difference in the pressure beneath the tips. Further the gradient elasticity approach of Han and co workers suggest no depth dependence for the spherical geometry and for the wedge tip geometry which is a cylindrical shape. Hence, while one might expect a tip effect on absolute modulus values at a given depth, the sphere and wedge shapes should not show depth dependence.…”
Section: Discussionmentioning
confidence: 96%
“…One recent proposal for depth-dependent moduli comes from the idea of a strain gradient elasticity [58][59][60][61][62][63], for which the Berkovich tip seems to exhibit a very large effect in soft materials. Hence, a Berkovich indenter was also used to probe the mechanical properties of the PETN single crystals.…”
Section: Indentation Measurements With the Berkovich Shaped Tipmentioning
confidence: 99%